Effects of Floral Scents and Their Dietary Experiences on the Feeding Preference in the Blowfly, Phormia regina - Maeda, Toru; Tamotsu, Miwako; Yamaoka, Ryohei; Ozaki, Mamiko (Frontiers in Integrative Neuroscience, 2015)
Abstract The flowers of different plant species have diverse scents with varied chemical compositions. Hence, every floral scent does not uniformly affect insect feeding preferences. The blowfly, Phormia regina, is a nectar feeder, and when a fly feeds on flower nectar, its olfactory organs, antennae, and maxillary palps are exposed to the scent. Generally, feeding preference is influenced by food flavor, which relies on both taste and odor. Therefore, the flies perceive the sweet taste of nectar and the particular scent of the flower simultaneously, and this olfactory information affects their feeding preference. Here, we show that the floral scents of 50 plant species have various effects on their sucrose feeding motivation, which was evaluated using the proboscis extension reflex (PER). Those floral scents were first categorized into three groups, based on their effects on the PER threshold sucrose concentration, which indicates whether a fly innately dislikes, ignores, or likes the target scent. Moreover, memory of olfactory experience with those floral scents during sugar feeding influenced the PER threshold. After feeding on sucrose solutions flavored with floral scents for 5 days, the scents did not consistently show the previously observed effects. Considering such empirical effects of scents on the PER threshold, we categorized the effects of the 50 tested floral scents on feeding preference into 16 of all possible 27 theoretical types. We then conducted the same experiments with flies whose antennae or maxillary palps were ablated prior to PER test in a fly group naïve to floral scents and prior to the olfactory experience during sugar feeding in the other fly group in order to test how these organs were involved in the effect of the floral scent. The results suggested that olfactory inputs through these organs play different roles in forming or modifying feeding preferences. Thus, our study contributes to an understanding of underlying mechanisms associated with the convergent processing of olfactory inputs with taste information, which affects feeding preference or appetite.